Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Wang, Qiang; Chen, Zhaoming; Zhao, Jun; Ma, Junwei; Yu, Qiaogang; Zou, Ping; Lin, Hui; Ma, Jinchuan (Journal of soils and sediments, 2022)
Purpose Biogas slurry (BS) is widely used as a valuable fertilizer for crop production. However, little is known about the effects of long-term BS application on potential pollution risk of heavy metals and bacterial community in paddy field. This study aimed to determine the accumulation and rice plant uptake of heavy metals (Cd, Cr, Pb, Cu, and Zn), as well as soil bacterial community composition following repeated BS application in a single rice cropping system. Materials and methods In this study, four treatments were included in a long-term field experiment: CK, no fertilizers; MF, mineral fertilizers, 270 kg urea-N ha –1 ; and two application rates of BS (BS1, 270 kg N ha –1 and BS2, 540 kg N ha –1 ). The heavy metals (Cd, Cr, Pb, Cu, and Zn) in soils and rice plants were measured by an inductively coupled plasma mass spectrometer and the soil bacterial community composition was analyzed using Illumina MiSeq sequencing of the 16S rRNA. Results and discussion Soil Zn concentrations were significantly greater in the BS treatments than in the MF treatment. Biogas slurry application significantly increased the heavy metals concentrations in rice plants, compared to the CK treatment. The concentrations of Cd and Pb in grain, and Cu and Zn concentrations in straw were significantly increased by the BS2 treatment compared to the MF treatment, respectively. However, the Cd, Cr, Pb, Cu, and Zn concentrations in grain and soil were all within the safety limits after long-term BS application. Application of BS and of MF resulted in similar bacterial alpha-diversities, and both increased them compared to the CK treatment. Fertilization significantly enhanced the relative abundances of phyla Proteobacteria , Actinobacteria , and Myxococcota but reduced that of Planctomycetota compared to the CK. While, there were no significant differences in those phyla among fertilized treatments. The relative abundances of genera Thiobacillus and Ellin6067 was decreased by the BS2 treatment compared to the MF treatment. Redundancy analysis (RDA) showed that soil organic carbon, available phosphorus and available potassium were the main factors shaping soil bacterial community composition. Spearman’s correlation demonstrated that soil Cd concentration had stronger correlation with some bacterial genera of Bryobacter , Vicinamibacteraceae , and Ellin6067 . Conclusions Overall, we conclude that BS application can be considered to substitute mineral fertilizers for rice production. However, the accumulation of heavy metals in paddy soil, especially for Zn, should be considered after long-term BS application.